Sirolimus Therapy and Dyslipidemia in Neonates and Infants: A Retrospective Cohort and Pharmacovigilance Analysis - Taniguchi, Akinobu; Chrétien, Basile; Maeda, Takashi; Ueda, Kazuto; Miura, Ryosuke; Tanaka, Ryuichi; SUZUKI, T; Muramatsu, Yukako; Sato, Yoshiaki; Nishida, Kazuki (Pediatric Drugs, 2026)
IMPORTANCE: Sirolimus is increasingly used for complex vascular and lymphatic anomalies in neonates and infants. While dyslipidemia is a known adverse effect in adults, the incidence, timing, and severity in this population remain poorly characterized. OBJECTIVE: The aim of this study was to evaluate the reporting odds and characteristics of sirolimus-associated dyslipidemia in neonates and infants compared with older populations. DESIGN, SETTING, AND PARTICIPANTS: This study combined a single-center retrospective cohort study and global pharmacovigilance analysis. The clinical cohort included neonates and infants treated with sirolimus at Nagoya University Hospital (October 2018-September 2025). The pharmacovigilance analysis utilized VigiBase (up to September 1, 2025) to perform age-stratified disproportionality analyses. MAIN OUTCOMES AND MEASURES: In the clinical cohort, lipid profiles (total cholesterol, LDL-C, triglycerides) were assessed pre- and post-treatment. In VigiBase, adjusted reporting odds ratios (aRORs) for dyslipidemia and time-to-onset (TTO) were estimated across age groups, adjusting for sex, region, and concomitant medications. RESULTS: The cohort included 10 patients (median age, 44.5 days). Post-initiation, 100% developed hypertriglyceridemia and 90% developed hypercholesterolemia. In VigiBase (17,802 sirolimus-related reports), the dyslipidemia reporting signal was highest in infants (28 days-23 months), with an aROR of 147.08 (95% CI 79.67-271.54), substantially exceeding that in adults aged 18-45 years (aROR 2.31; 95% CI 1.75-3.06). Among infant reports with available TTO data, median TTO was 11.0 days (IQR 5.5-15.8), compared with 29.5 days in adults. CONCLUSIONS AND RELEVANCE: Neonates and infants showed a markedly stronger dyslipidemia reporting signal than older age groups, and lipid abnormalities were common in the clinical cohort. These findings support baseline lipid assessment and early monitoring after sirolimus initiation in very young patients, including within the first two weeks of therapy. The pharmacovigilance findings should be interpreted as hypothesis generating.